PENGEMBANGAN BAKMIE (BAHAN AJAR INTERAKTIF BERBASIS MICROSITE) PADA MATERI SEJARAH KERAJAAN BERCORAK ISLAM DI INDONESIA UNTUK KELAS IV SD - Muhammad Agung Nur Huda; Riska Pristiani; Oktaviani Adhi Suciptaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop BAKMIE (Interactive Learning Materials Based on Microsite) on the material of the history of Islamic kingdoms in Indonesia for grade IV of elementary school. This study refers to the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study included 27 grade IV students and one teacher at SD Islam Terpadu Iqro Malang Regency. Data collection techniques involved observation, validation questionnaires from experts, questionnaires to determine teacher and student responses, and learning outcome tests consisting of pre-tests and post-tests. The validation results showed that the BAKMIE media was declared very valid by media experts (93.4%) and material experts (95.7%). This media was also declared very practical based on teacher responses (91.3%). The results of the effectiveness test showed an increase in student learning outcomes from an average pre-test score of 58.3 to 84.5 in the post-test with an N-gain score of 0.62 (moderate category). Thus, BAKMIE has proven to be feasible, practical, and effective for use in science learning, and supports interactive and contextual learning processes in accordance with the Merdeka Curriculum.